High sedentary behavior and low physical activity among adults in Afghanistan: results from a national cross-sectional survey - Pengpid, Supa; Noormal, Ahmad Siyar; Peltzer, Karl (Frontiers in Public Health, 2023)
Objective: The study aimed to evaluate the prevalence and correlates of sedentary behaviour and combination of sedentary behaviour and low physical activity among adults in Afghanistan in 2018.Methods: This was a national representative cross-sectional study. The study utilized the data from Afghanistan STEPS survey 2018, where 3956 adults (ages between 18-69 years) were interviewed at community-dwelling level. Using the Global Physical Activity Questionnaire, we have calculated the sedentary behaviour and physical inactivity. Logistic regression was applied to investigate factors associated high sedentary behaviour and low physical activity.Results: Approximately half of the participants (49.8%) exhibited high levels of sedentary behaviour, 40.3% low physical activity and 23.5% had both high sedentary behaviour and low physical activity. Adjusted logistic regression analysis revealed that individuals who were employed (AOR: 0.34, 95% CI: 0.13-0.88) or self-employed (AOR: 0.60, 95% CI: 0.38-0.94) had significantly lower odds of both high SB and low physical activity than those whose work status was unpaid. Furthermore, older age (AOR: 1.75, 95% CI: 1.35-2.28), urban residence (AOR: 3.17, 95% CI: 1.72-6.05), having 4 or 5 adult household members (AOR: 1.77, 95% CI: 1.21-2.58) and being underweight (AOR: 1.78, 95% CI: 1.02-3.12) were found to be associated with high sedentary behaviour. Moreover, factors such as female sex, having 4 or 5 or 6 or more adult household members, urban residence, overweight, and diabetes were positively associated, and male sex (AOR: 0.24, 95% CI: 0.12-0.51), being employed (AOR: 0.34, 95% CI: 0.13-0.88) or self-employed (AOR: 0.60, 95% CI: 0.38-0.94) were negatively associated with the occurance of combination of high sedentary behaviour and low physical activity.Half of the participants had high sedentary behaviour, and one in four had both high sedentary behaviour and low physical activity together. These findings emphasize the importance of targeted interventions aimed at reducing sedentary behaviour and promoting physical activity, particularly among vulnerable populations such as females, individuals from lower socioeconomic background, urban residents, and those with chronic conditions. Addressing these factors can contribute to improving public health outcomes and reducing negative health impacts of sedentary behaviour in Afghanistan.